Assessing the economic benefits of sustainable land management practices in Bhutan - Nkonya, Ephraim M.; Srinivasan, Raghavan; Anderson, Weston; Kato, Edward (International Food Policy Research Institute, 2014)
This study was conducted with the objective of determining the returns to sustainable land management (SLM) at the national level in Bhutan. The study first uses satellite data on land change (Landsat) to examine land use change in 1990–2010 and its impact on sediment loading in hydroelectric power plants. The study then uses the Soil and Water Assessment Tool (SWAT) model to analyze the impact of land use change and land management on sediment loading. The results from the land use change and SWAT analyses are used to assess the economic benefits of SLM.